Green Tech and Human Dynamics: Transforming Indonesia’s Waste Industry with VR, AR, and Renewable Energy Innovations - Manurung, John Sihar (International Journal of Energy Economics and Policy, 2024)
The objective of this study is to assess the impact of implementing virtual reality technology, augmented reality, renewable energy, and green leadership on industrial sustainability in waste management in Indonesia. Additionally, this study aims to examine the role of HR attitudes as a moderating variable in this context. The study focuses on leaders of large and medium-sized companies in Indonesia in 2022. The study examines several variables, including virtual reality, augmented reality, the application of renewable energy, and the application of green leadership. The study also considers exogenous variables such as industrial sustainability in waste management in Indonesia, and moderating variables such as HR behaviour. The data analysis employs SEM analysis using SMART PLS 3.0 software. The study methodology employed entails a quantitative descriptive approach utilising data analysis through the structural equation model (SEM) method. The data processing using the SEM method is conducted with the PLS application. Based on the findings of previous studies, it can be inferred that virtual reality, augmented reality, renewable energy, and green leadership have a partial impact on the sustainability of industrial businesses involved in waste treatment in Indonesia. Additionally, these variables also influence the behaviour of HR in responding to technological changes and the adoption of renewable energy in waste management companies in Indonesia. The variables of virtual reality, augmented reality, renewable energy, and green leadership have a simultaneous impact on the sustainability of industrial businesses involved in waste treatment in Indonesia. This impact is mediated by the HR behaviour in response to changes in technology adoption and the use of renewable energy in waste management companies in Indonesia. By implementing virtual reality and augmented reality technologies, as well as embracing the latest energy solutions and fostering a green leadership mind-set, companies can drive changes in human resource behaviour. This will enable employees to continuously adapt to technological advancements, particularly in smartphone applications, and leverage them to enhance existing businesses and ensure their sustainability. Moreover, the promotion of green energy will induce a shift in human resource practices towards consistently utilising eco-friendly energy sources and embracing sustainable leadership models within each organisation. This will ensure the long-term survival of the organisations and mitigate environmental harm caused by global warming.